Micro Climate Humidity in Nursery and Production Various Varieties Melon (Cucumis melo L.) in PKHT Tajur II - Dirgha A. S. Adinegara; Rini Hidayati; . Perdinan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2017)
Micro-climatic conditions may affect the growth and productivity of different genotypes of melon farm. This study aims to assess the effect of different moisture conditions in the melon’s nursery to the growth and production of different melon’s genotypes. To observe the effect of moisture, we monitored agronomical (leaf-area index, plant height, fruit weight) and micro-meteorological (transpiration, radiation interception) parameters for two treatments i.e. without modification of moisture (control) and with modification of moisture for period August-November 2015 at the Experimental Garden of IPB in Tajur II-Bogor. Totally, twelve genotypes of melon were used in the study. We found that a transpiration rate was reduced under the control treatment. It appears that the humidity treatment has a greater effect on both measured parameters. The plant height during the germination phased was affected by the humidity treatment, which was confirmed by the two statistical tests (ANOVA and t-test). In addition, our results showed that the treatment had influenced the harvesting time. Under the control treatment, melon seems to have a shorter time to harvest (about 61-63 days after planting), but a lower fruit weight. On the other hand, the modified humidity resulted in a longer time to harvest (68-71 days after planting) and a higher fruit weight. Further, with the treatment we found some genotypes that were potentially able to produce high yield, and some genotypes that were more resistant to dry conditions but they produced a relatively high yield.